Correction: The World Health Organization Fetal Growth Charts: A Multinational Longitudinal Study of Ultrasound Biometric Measurements and Estimated Fetal Weight. - Torvid Kiserud; Gilda Piaggio; Guillermo Carroli; Mariana Widmer; José Carvalho; Lisa Neerup Jensen; Daniel Giordano; José Guilherme Cecatti; Hany Abdel Aleem; Sameera A Talegawkar; Alexandra Benachi; Anke Diemert; et al. (PLoS Medicine, 2021)
[This corrects the article DOI: 10.1371/journal.pmed.1002220.].